Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1088/0004-6256/145/3/73
|View full text |Cite
|
Sign up to set email alerts
|

On the Radio and Near-Infrared Jet of PKS 2155–304 and Its Close Environment

Abstract: PKS 2155-304 is one of the brightest BL Lac object in the sky and a very well studied target from radio to TeV bands. We report on high resolution (∼0.12 arcsec) direct imaging of the field of PKS 2155-304 using adaptive optics near-IR observations in J and Ks bands obtained with the ESO multi-conjugate adaptive optic demonstrator (MAD) at the Very Large Telescope. These data are complemented with archival VLA images at various frequencies to investigate the properties of the close environment of the source. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…Optical imaging of the field of PKS 2155-304 revealed the presence of a moderated overdensity of galaxies (Falomo et al 1991;Falomo, Pesce, & Treves 1993;Wurtz et al 1997). This finding is corroborated by the detection in high-resolution NIR images of 5 galaxies located within ∼20 ′′ (∼40 kpc at z=0.116) from PKS 2155-304 (Liuzzo et al 2013) and by spectroscopic observations of some of the sources (Falomo et al 1991;Falomo, Pesce, & Treves 1993). We here present a comprehensive study of the field of PKS 2155-304 using new spectra gathered with the Magellan Telescope and archival data from Prochaska et al (2011).…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Optical imaging of the field of PKS 2155-304 revealed the presence of a moderated overdensity of galaxies (Falomo et al 1991;Falomo, Pesce, & Treves 1993;Wurtz et al 1997). This finding is corroborated by the detection in high-resolution NIR images of 5 galaxies located within ∼20 ′′ (∼40 kpc at z=0.116) from PKS 2155-304 (Liuzzo et al 2013) and by spectroscopic observations of some of the sources (Falomo et al 1991;Falomo, Pesce, & Treves 1993). We here present a comprehensive study of the field of PKS 2155-304 using new spectra gathered with the Magellan Telescope and archival data from Prochaska et al (2011).…”
Section: Introductionsupporting
confidence: 69%
“…In addition to multi-object spectroscopy, we acquired a long-slit spectrum of the two closest galaxies to PKS 2155-304 (i.e., G1 and G5; Falomo, Pesce, & Treves 1993;Liuzzo et al 2013). Data were gathered during the same night of the multi-object spectroscopy with a seeing of ∼0.…”
Section: Long-slit Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The grey points are the data from the 2008 observation campaign (Aharonian et al 2009) shown for comparison. Black points are the radio data from Abdo et al (2010) and Liuzzo et al (2013). The dashed blue line is the synchrotron emission and the orange line is the IC emission.…”
Section: Broad-band X-ray Spectrummentioning
confidence: 98%
“…The modelling was performed on the epochs presented in this work (1-5) with UV, X-ray, GeV, and TeV data. Radio data from Abdo et al (2010) and Liuzzo et al (2013) were taken from the NED 10 . The radio emission could originate from another location in the jet, or from the emission zone, and is therefore considered as an upper limit in the model.…”
Section: Leptonic Modelling: One Zone Synchrotron Self-comptonmentioning
confidence: 99%